Turnour necrosis factor stimulates endothelin-1 gene expression in cultured bovine endothelial cells - Silvia Orisio; Marina Morigi; Carla Zoja; Norberto Perico; Giuseppe Remuzzi (Mediators of Inflammation)
We have studied the effect of human recombinant tumour necrosis factor-α (TNF-α) on gene expression and production of endothelin-1 in cultured bovine aortic endothelial cells. TNF-α (10 and 100 ng ml−1) increased in a time dependent manner the preproendothelin-1 mRNA levels in respect to unstimulated endothelial cells. TNF-α induced endothelin-1 gene expression was associated with a parallel increase in the release of the corresponding peptide in the culture medium. These findings suggest that the enhanced synthesis and release of endothelin-1 occurring in conditions of increased generation of TNF, may act as a modulatory factor that counteracts the hypotensive effect and the excessive platelet aggregation and adhesion induced by TNF.